Eficacia y seguridad de la dapoxetina en el tratamiento de la eyaculación precoz: una sinopsis de revisiones sistemáticas - Mezones Holguin, Edward (2019)
Introduction: Premature ejaculation (PE) is a frequent condition for which there are several pharmacological therapies at present. Objective: To evaluate the available scientific evidence regarding the efficacy and safety of Dapoxetine in the treatment of PE. Methods and objective: We developed a synopsis of systematic reviews (SR) of randomized clinical trials (RCTs) that included male patients with the diagnosis of PE. We carried out a primary search without any language restriction in Pubmed-Medline, WOS, EMBASE, SCOPUS and Cochrane Library until March, 2019. R-AMSTAR was used for quality assessment. Selection, quality assessment and extraction were carried out blindly and independently by two authors and resolved by discussion of referral to a third author. Results: We identified 16 SR: five network metaanalyses (NMA), ten traditional meta-analyses (TMA), and a SR without meta-analysis. In the NMA, Dapoxetine was compared with other pharmacological and non-pharmacological therapies such as placebo; in two of them, it was concluded that the use of Dapoxetine, at a dose of 30 mg, was as effective as other alternatives, but with a better safety profile, mainly when it was used as a needed therapy. In the seven (TMA), in which Dapoxetine was compared with placebo, it was reported that, at different doses (60mg or 30 mg), the effect of Dapoxetine was higher in the latent period of intravaginal ejaculation. In the three remaining meta-analyses, other medicines were included as comparators, where Dapoxetine demonstrated to have good efficacy profile and to be one of the highest safety profiles. A potential advantage of Dapoxetine identified in SR is its use as needed therapy. Conclusion & recommendation: The evidence discussed shows that dapoxetine is efficacious and has a good safety profile in the treatment of PE in adults. This evidence should be considered for the implementation of clinical practical guides on PE and its management update.